Rainfall uncertainty for extreme events in NWP downscaling model - Yunqing Xuan (Hydrological Processes, 2011)
Extreme rainfall events are among the very foci of the stakeholders and policy makers in flood risk management. This paper reveals the potential of using numerical weather prediction in this context. It was one of the first in this area that has systematically studied the NWP on extreme rainfall in the context of hydrological use.